(untitled) (Nexo Revista Científica, 2012)
This study was carried out east of Lake Nicaragua. To identify remaining areas of forest with high potential for environmental service. Six fragments of vegetation were selected. Within each fragment was identified representative vegetation, and here was established a temporal measurement plot (10,000 m2). Was taken information from species and diameter measured at breast height (DBH) for all individuals with a diameter greater than 2.5 cm. The variables studied were: Diversity, use and management of forest, carbon stocks. Simpson and Shannon-Wiener indices agree that fragment 3 is the most diverse presenting 21 families, 25 genera and 30 species. Forest areas provide various environmental services. Biodiversity indices suggest that most of these fragments harbor an important diversity of species of trees and shrubs. DOI: http://dx.doi.org/10.5377/nexo.v25i1.782 Nexo Revista Científica,Vol. 25, No. 01, pp.02-08/Junio 2012